Aplicabilidade clínica do subconjunto terminológico da CIPE® para a mulher idosa com vulnerabilidade relacionada ao HIV/Aids: desenvolvimento de uma teoria de médio alcance - Santos, Márcia Cristina de Figueiredo (2022)
Introduction: Faced with the epidemiological transition of HIV/aids, with the feminization and aging of the affected population, Nursing must be equipped with the potential to act in the care of this clientele. Thus, it needs instruments to record the practice that favor a standardized language. The clinical applicability of the ICNP® terminology subset for elderly women with vulnerability related to HIV/aids has the potential to foster its clinical validation, joining efforts in the face of this need and allowing the development of a middle-range theory. Objective: To assess the clinical applicability of the ICNP® Terminological Subset for elderly women with HIV/aids related vulnerability, structuring a middle-range theory. Methods: A multi-method study, developed through human mapping of the ICNP® terminology subset for elderly women with HIV/aids-related vulnerability in the ICNP® 2019/2020; structuring and validation of the instrument to assess the clinical applicability of the terminology subset; operationalization of the same through clinical case studies; and development of a Medium Range Theory for the self-care of elderly women with vulnerability related to HIV/aids. It was approved by the Research Ethics Committee under protocol N. 4.429.145. Results: A total of 52 NDs were mapped with the ICNP® 2019/2020, through the analysis of the degree of equivalence, and 221 NIs, composing the updated version of the terminological subset. Validation of the structured instrument was obtained to evaluate the clinical applicability of the terminology subset by 13 experts, with an overall content validity index (CVI) = 1. Nine clinical case studies were carried out to assess the clinical applicability of the subset, and 32 were identified. diagnoses/nursing results and 114 nursing interventions, allowing the theoretical induction of the Nursing Theory for the self care of elderly women with vulnerability related to HIV/aids – TENFAIVHI. Conclusions: The study's thesis is confirmed through the operationalization of the ICNP® terminological subset for elderly women with HIV/aids-related vulnerability, which supported the development of a conceptual basis in Nursing.